PROTECTION OF THE WIFE AS A VICTIM OF CRIME IN DOMESTIC VIOLENCE: (Study in Police Resort Blitar) - Cindy Tiara Gracia Yoseph; Teguh Suratman; Riski Febria Nurita (Transpublika Publisher, 2022)
Domestic violence is an unlawful act, and if it is specifically regulated by the Criminal Code or a particular law, it can be classified as a criminal offense. This study focuses on the